NILAI PENDIDIKAN KARAKTER DALAM LAGU ANAK KARYA PAK KASUR - Muammar, Khafid (sarasvati, 2020)
Character education is a discourse that must be introduced from an early age. Its existence is important in shaping civilized and dignified human beings, as stated in article 3 of the UU Sisdiknas. Character education is translated into nine pillars of character values, namely (1) love of God and all of His creation, (2) independence and responsibility, (3) honesty / trustworthiness, wisdom, (4) respect and courtesy, (5) generous, like helping and mutual cooperation, (6) confident, creative and hardworking, (7) leadership and justice, (8) kind and humble, (9) tolerance, peace and unity. Various methods are used to make it easier to get character education, one way is through children's songs. Children's song is a song specially created for children. The simplicity of time, lyrics, and melody is the hallmark of children's songs. Pak Kasur's songs contain moral teachings that can help build children's character. Pelangi-pelangi, Bangun Tidur, Peramah dan Sopan, serta Bumiku Indonesia dan Anak Indonesia are some songs that clearly contain character values. In the end, the existence of children's songs is important to always be developed and updated. Regarding character education, it is necessary to revitalize children's songs that have been modified and created new ones according to the times.